The repercussions of vaping use on health: Integrative literature review (Research, Society and Development, 2024)
Introduction E-cigarettes are as harmful to one's health as smoking other tobacco-based products. Objective: Review the main health effects of vaping, focusing on the stomatognathic system. Methodology For this purpose, the authors carried out a literature review using an integrative approach, checking data available from 2015 to 2023 on the databases Pubmed, Virtual Health Library, and Scielo, using the following keywords: 'Vaping,' 'Electronic Nicotine Release System', 'e-cig,' 'Health' and 'Oral Health.' Results The authors applied eligibility criteria to select 31 out of 451 articles they found as a result of their search. The findings showed that vaping is associated with inflammatory-based morbidities such as cardiovascular, respiratory, and periodontal diseases. Conclusion Vaping has adverse effects on its users' health and may constitute a public health issue that requires further discussion and debate to be resolved.